PEMANFAATAN TEKNOLOGI DATA MINING DALAM MENENTUKAN EFEKTIFITAS PENYEBARAN BROSUR - Fajar Ardanu (Jurusan Teknik Informatika, 2014)
During this time many organizations or companies that perform marketing productsusing brochures . The spread of this brochure done anywhere and at any time regardless of theamount . The purpose of this course the distribution of brochures to attract people to buy aproduct from a company or organization . However , companies often do not pay attention towhen the time is right to make the distribution of brochures where and who are the targetconsumers of the company in accordance with the products on offer , so it designed a systemwith data mining technology that can be used to determine the distribution of brochuresschedule , location deployment brochures and anyone taget consumer . The methodology usedin the making of this application is a waterfall methodology . While the software used in buildingthis application is c45 algorithm and its implementation in the form of desktop built using VisualBasic 6.0 and SQL Server 2000 . Application of data mining technology using c45 algorithmgives information in determining the effectiveness of the distribution of brochures . Thisapplication also comes with a data member and employee information .Keywords : brochure, data mining, aplication, algoritma c45